Intelligent Manufacturing & Mechatronics Proceedings of Symposium, 29 January 2018, Pekan, Pahang, Malaysia (Lecture Notes in Mechanical Engineering,, 2018)
This book presents the proceedings of SympoSIMM 2018, the 1st edition of the Symposium on Intelligent Manufacturing and Mechatronics. With the theme of "Strengthening Innovations Towards Industry 4.0", the book comprises the studies towards the particularity of Industry 4.0's current trends. It is divided into five parts covering various scopes of manufacturing engineering and mechatronics stream, namely Intelligent Manufacturing, Robotics, Artificial Intelligence, Instrumentation, and Modelling and Simulation. It is hoped that this book will benefit the readers in embracing the new era of Industrial Revolution 4.0.